Acanthaceae: Mendoncioideae of Mexico - Daniel, Thomas F. (Instituto de Ecología, A.C., 1992)
Subfamily Mendoncioideae of the Acanthaceae is represented in México by two spedes, Mendoncia guatemalensis and M. retusa. The former spedes is reported from México for the first time. The initial description of flowers of M. guatemalensis is presentad. A lectotype for M. retusa 'is designated. Both spedes are described and illustrated; a key is provided to distinguish them; and the distribution of each spedes in México and northern Central America is shown on a map.